A Comprehensive Analysis of Supply Chain Collaboration, Technological Upgrading, and Market Demand as a Framework for Increasing Competitiveness - Tan, Haoli (International Journal of Global Economics and Management, 2024)
The purpose of this study is to evaluate how supply chain collaboration, technical advancement, and consumer demand affect manufacturing firms' ability to compete in Guangdong Province. The particular goals include testing the relationship between supply chain cooperation, technological innovation, and market demand development; evaluating technology maturity, adaptability, and cost-effectiveness; assessing supply chain coordination efficiency, supply chain risk management capability, and supply chain innovation capability; analyzing accuracy of market demand forecasting, speed of market demand response, and customer demand diversity; and developing a comprehensive framework for enhancing enterprise competitiveness. Using surveys, data analysis, and empirical research, this study uses a mixed-method approach that combines quantitative and qualitative analysis to examine the links between the variables and offer management recommendations.